Variable strategies for designing management structures in development construction projects - POKOLENKO, Vadym; SHCHERBAN, Bohdan; TSYMBALISTY, Yurii; HERASYMCHUK, Yaroslav (Ways to Improve Construction Efficiency, 2025)
This work is devoted to the study of variable strategies for designing management structures in development construction projects. In the conditions of dynamic development of the construction industry and increasing complexity of development projects, there is a need to adapt management models to changing market conditions, regulatory requirements and technological challenges. The effectiveness of the management structure directly affects the implementation time, budgeting, quality of work performed and the overall competitiveness of the development project. The main concepts of forming organizational structures for managing construction development projects are considered. Three key approaches are distinguished: hierarchical, matrix and hybrid. The hierarchical model is characterized by centralized decision-making, which promotes control, but limits flexibility. The matrix approach involves the distribution of responsibility between functional units, which increases coordination, but can lead to conflicts between management levels. The hybrid approach combines the advantages of both models, providing an optimal balance between control and adaptability. The article analyzes the factors influencing the choice of a particular management structure, in particular the scale of the project, the level of technological complexity, the availability of financial resources, regional features, as well as the strategic goals of the developer. A comparative analysis of the effectiveness of the application of different approaches in the context of ensuring optimal resource allocation, minimizing risks and increasing productivity is carried out. Special attention is paid to modern trends in the digital transformation of management structures in construction projects. The impact of automated management systems, BIM technologies (Building Information Modeling) and artificial intelligence on the optimization of project processes, increasing forecasting accuracy and improving communication between project participants is studied. The practical significance of the study lies in the development of recommendations for the selection and adaptation of the optimal management structure in accordance with the specifics of a particular development project. The proposed approaches can be used to improve the efficiency of planning, coordination and implementation of construction projects in modern conditions.